The Role of EGFR, Hepatocyte Growth Factor Receptor (c-Met), c-ErbB2 (HER2-neu) and Clinicopathological Parameters in the Pathogenesis and Prognosis of Chordoma - Zeynep TOSUNER; Zeynep TOSUNER; Türker KILIÇ; Baran YILMAZ (Federation of Turkish Pathology Societies, 2017)
Objective: Chordoma is a rare malignant bone tumor with a poor outcome. Although radiotherapy and gamma knife surgery have been used for treatment, providing a cure for the tumor is not easy, because of the frequent recurrences. Molecular targeted therapy against tyrosine kinases has been effective in the treatment of malignancies such as breast and lung cancers and brain tumors. We aimed to analyse the histopathological features of chordomas and the immunoexpression profiles of the three receptor tyrosine kinases of EGFR, c-Met and c-Erb-B2 in chordomas. We have correlated these results with recurrence and overall survival status of the patients. Material and Method: We studied 49 chordoma patients in order to evaluate the histopathological features and immunohistochemical stainings by EGFR, c-Met and c-ErbB2 antibodies. Of the 49 patients, follow up data was available for 40 patients. Clinical data of the patients were correlated with histopathological features and survival analysis was performed. Results: The immunostaining rate by EGFR and c-Met was 73.5% and 12.2% respectively. None of the cases showed immunoreactivity by c-ErbB2 (0%). Of the 40 cases, 17 cases showed recurrences. EGFR expression was detected in 14 recurrent (14/17) and 17 non-recurrent cases (17/23). Four of the 17 recurrent cases (4/17) were positive by c-Met, while none of the non-recurrent cases (0/23) were positive by this antibody. Significantly, all cases with positive c-Met expression showed recurrences (p<0.05). Conclusion: Our study indicates that EGFR expression is detected in the majority of chordoma cases. c-Met expression can be used as a prognostic indicator for chordoma.